Copper Ferrite Superparamagnetic Nanoparticle-Catalyzed Cross-coupling Reaction to Form Diindolylmethane (DIM): Effect of Experimental Parameters - Oanh T.K. Nguyen; Ha Trong Pha; Huynh Dang Khoa; Duy Chinh Nguyen; Nguyen Thi Hong Tam (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
Superparamagnetic copper ferrite (CuFe2O4) nanoparticles were utilized as a heterogenous catalyst for the cross-coupling reaction of indole to form 3,3’-diindolylmethane (DIM) as the desirable product. High reaction yield, at around 82%, was achieved under optimal conditions. The CuFe2O4 material could be easily separated from the reaction mixture by an external magnetic field and could be reutilized several times without a significant decrease in catalytic activity. We also showed that no sites of catalyst material leached into reaction solution was detected. To our best knowledge, the above cross-coupling reaction was not previously conducted under catalysis of superparamagnetic nanoparticles. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).